Interdisciplinary perspectives on designing, understanding and evaluating digital technologies for autism. Issue 1 (20th March 2017) - Parsons, Sarah; Yuill, Nicola; Brosnan, Mark; Good, Judith
Abstract : Purpose: Interdisciplinary perspectives and collaboration in technology research are regarded as vital for producing effective and usable solutions that meet real needs. The purpose of this paper is to draw upon the fifth seminar in an Economic and Social Research Council funded series in the UK on "Innovative Technologies for Autism". This seminar focused on the contributions that different disciplines can make to the field of autism and technology, and offers some interesting avenues for future research. Design/methodology/approach: A synthesis of key messages from the speakers' talks is presented, interspersed with comments and observations from delegates which were written on post-it notes during the day and shared amongst the group. Findings: Interdisciplinarity can be conceptualised in many different ways and is not simply about academic contributions. Collaborative research involving genuine stakeholder participation can provide fertile grounds for respecting and exploring individual differences and needs. Investigating the uses of existing technologies as well as developing innovative ideas and prototypes through inclusive design are important avenues for future research. Originality/value: This paper offers a rare glimpse into a range of perspectives within a broad field of research and draws out some important connections between these different viewpoints. There are valuable avenues for collaboration and further exploration that would extend research in productive ways.